Synthesis of adeno-associated virus structural proteins requires both alternative mRNA splicing and alternative initiations from a single transcript. - Becerra, S P (1988)
The three adeno-associated virus type 2 (AAV2) structural proteins (A, B, and C) are specified by transcripts generated from the most-rightward promoter (p40). Protein C (60 kilodaltons [kDa]), the most abundantly produced, is entirely contained within B (72 kDa) which, in turn, is contained within A (90 kDa). Although neither of the known structures of p40 transcripts, an unspliced 2.6-kilobase (kb) RNA and a spliced 2.3-kb RNA, possesses an AUG-initiated open reading frame that accounts for the synthesis of proteins A and B, recent evidence indicates that B is initiated by a unique eucaryotic initiation codon (ACG) (S.P. Becerra, J.A. Rose, M. Hardy, B. Baroudy, and C.W. Anderson, Proc. Natl. Acad. Sci. USA 82:7919-7923, 1985). In the present study, we analyzed the in vitro translation of AAV capsid proteins from synthetic transcripts and the in vivo expression of AAV mRNA and capsid proteins in 293 cells transfected with AAV DNA constructs. The results demonstrated that AAV transcripts contain only one functional 5' splice donor site, that synthesis of capsid proteins from the unspliced 2.6-kb transcript is very inefficient, that transcripts without the intervening sequence (IVS) (i.e., the 2.3-kb RNA) do not produce protein A but effectively synthesize proteins B and C, and that protein A is actively synthesized from transcripts which contain the last 34 bases of the IVS. Protein A initiates within this 34-base segment in reading frame 1, apparently with the AUG codon at nucleotide 2203, and then elongates into the B and C open reading frame. Because A is inefficiently synthesized from the 2.6-kb transcript, we conclude that an effective A transcript is generated by alternative splicing and that the alternative 3' acceptor site may lie at nucleotide 2200 within a context of...CAG]GTA. The levels of B and C produced by a synthetic transcript devoid of the IVS suggest that the known 2.3-kb RNA is the main source of these proteins and indicate that this single RNA species expresses both proteins by alternative use of their respective initiation codons.